Lipoprotein-associated phospholipase A2 in relation to lipid markers: A pan-India correlation study - Iyer, Sandhya; Kushawaha, Rajkumar; Sinkar, Prachi; Selvaraj, Sivakumar; Velumani, Amruta (Asian Journal of Medical Sciences, 2019)
Background: Conventional serum markers are routinely recommended to assess heart health. However, many new biochemical markers like lipoprotein-associated phospholipase A2 (Lp-PLA2) has been studied as an efficient cardiac risk marker. Our report is an attempt to present correlation between traditional lipid markers and Lp-PLA2 in a pan-India cohort.Materials and Methods: The study cohort included a total of 10347 pan-Indians including 5945 males and 4402 females respectively. The serum lipid parameters estimated include triglycerides, LDL- and HDL-cholesterol as well as total cholesterol by the technology of photometry.Results: The frequency of high Lp-PLA2 detected in our study was 6.4% and the frequency between males at 9.3% and females at 2.5% was detected to be significant at p